2008
DOI: 10.1124/dmd.107.018424
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Boswellic Acids in Vitro and in Vivo

Abstract: ABSTRACT:Boswellia serrata resin dry extract is among the few herbal remedies designated with an orphan drug status for the treatment of peritumoral brain edema. In addition, boswellic acids (BAs), the main active ingredients of B. serrata extracts, have potent antiinflammatory properties, and may represent promising agents for the treatment of inflammatory diseases. Pharmacokinetic studies, however, revealed poor bioavailability, especially of 11-keto-␤-boswellic acid (KBA) and 3-acetyl-11-keto-␤-boswellic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 18 publications
(30 reference statements)
6
66
0
Order By: Relevance
“…It was further shown that boswellic acids possess potent anti-inflammatory properties in vitro by inhibiting 5-lipoxygenase, human leukocyte elastase, and the NF-jB pathway. 10,11 Cathepsin G was identified as another target of boswellic acids. 11 In clinical research, positive effects of boswellic acids in the treatment of inflammatory diseases could be shown.…”
Section: Discussionmentioning
confidence: 99%
“…It was further shown that boswellic acids possess potent anti-inflammatory properties in vitro by inhibiting 5-lipoxygenase, human leukocyte elastase, and the NF-jB pathway. 10,11 Cathepsin G was identified as another target of boswellic acids. 11 In clinical research, positive effects of boswellic acids in the treatment of inflammatory diseases could be shown.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, AKBA and KBA failed to suppress PGE2 formation in human whole blood and in rats, despite significant inhibition of mPGES1 in the cellfree assay. The failure of KBA and AKBA to suppress LT and PGE2 formation in vivo could be related to the marginal permeability of AKBA and moderate absorption of KBA (Kruger et al, 2009), resulting in poor bioavailability (Kruger et al, 2008) with fairly low plasma concentrations (0.3 and <0.1 mM) (Buchele and Simmet, 2003;Tausch et al, 2009). The marked loss of activity of AKBA in whole blood might be related to its strong plasma protein binding .…”
Section: Discussionmentioning
confidence: 99%
“…According to the published studies, 25 mg/kg KBA administered to rats (corresponding to about 350 mg B. serrata extract/kg) could reach to physiological concentrations in the plasma and brain [14,15]. Vehicle of 2 ml/kg physiological saline (vehicle + I/R group) and 25 mg/kg KBA (KBA+I/R group) were given 1 h after reperfusion.…”
Section: Middle Cerebral Artery Occlusion Modelmentioning
confidence: 99%